ANALYSIS OF THERMAL CONDUCTION AT MELTING OF METAL BRICKS IN LIQUID BATH. MESSAGE 2. MODELING AND CALCULATION OF PROCESS OF THE ALLOYED STEEL BRICKS MELTING IN MODEM MELTING AGGREGATES - V. I. Timoshpolskij; Ju. S. Postohiik; D. N. Andrianov; O. A. Kondrasheva; R. B. Vais (Литьë и металлургия)
The methods of calculation of duration of the metallic bricks heating and melting in liquid bath, taking into account variability of thermal-physical characteristics of metal due to temperature, is developed.